Molecular phenotypes of ductal carcinoma-in-situ and invasive ductal carcinoma: A comparative study - Shilpa Gupta; Lopamudra Deka; Ruchika Gupta; Leela Pant; Sompal Singh (Wolters Kluwer Medknow Publications, 2012)
Aims and Objectives: This study was aimed at analyzing the prevalence of molecular phenotypes in invasive ductal carcinoma (IDC) and coexisting ductal carcinoma-in-situ (DCIS) and to correlate with clinicopathological features. Materials and Methods: In this study, 75 cases of IDC with coexisting DCIS were included. Molecular phenotype was determined using expression of estrogen receptor, progesterone receptor, HER2/neu, and cytokeratin 5/6. Statistical analysis was performed for correlation between molecular phenotypes and clinicopathologic parameters. Results: Of the 75 cases, the invasive component in all cases was IDC-not otherwise specified. About one-third of our patients were post-menopausal. The most common molecular phenotype was luminal A (45.3%) followed by HER2-expressing type (24%). In all cases, the molecular phenotype was identical in DCIS and the invasive component. HER2-expressing tumors were found to be larger in size with frequent nodal involvement. On statistical analysis, tumor size and grade were found to correlate with the molecular phenotype. Conclusion: In conclusion, the molecular phenotype in DCIS correlates well with that of coexisting IDC, suggesting that DCIS is a precursor lesion in these tumors. This correlation of molecular phenotype can be utilized in prediction of phenotype of the invasive component in a case with in-situ carcinoma.